PoRT consensus mechanism for energy trading system of new energy vehicles - ZHANG Haibo; LI Jiaqi; LIU Kaijian; LI Fangwei (Tongxin xuebao)
A reputation value proof consensus mechanism based on travel verification under blockchain was designed to address privacy leakage and other transaction security issues that easily occurred in the energy trading system of new energy vehicles during the trading process. Firstly, the RSU was chosen by the trusted authority to serve as nodes for building the blockchain network. Then, the proof of reputation value based on travel verification (PoRT) was used to ensure the iterative update of the distributed reputation value database by the vehicle through three stages, location signature determination, mileage verification, reputation value judgment and update to ensure sustainable operation of the energy trading system. The experimental results show that compared with energy trading system using other consensus mechanisms, the proposed mechanism has higher security and lower transaction latency when facing common attacks in the Internet of vehicles.